2013
DOI: 10.1158/2159-8290.cd-12-0361
|View full text |Cite
|
Sign up to set email alerts
|

ARID1A Mutations in Cancer: Another Epigenetic Tumor Suppressor?

Abstract: While disordered chromatin organization has long been recognized as a feature of cancer, the molecular underpinnings of chromatin structure, epigenetic regulation, and their relationships to transcription are only beginning to be understood. Cancer genome sequencing studies have revealed a novel theme: frequent mutation of epigenetic regulators. Among these, the ARID1A/BAF250A subunit of the SWI/SNF (BAF) chromatin remodeling complex has emerged as recurrently mutated in a broad array of tumor types. We review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
316
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(337 citation statements)
references
References 59 publications
(120 reference statements)
19
316
1
1
Order By: Relevance
“…Furthermore, in EC, the majority of previous studies have focused on the loss of ARID1A expression as determined by immunohistochemistry or gene sequencing of mutations (7)(8)(9)(10)(11). Therefore, it remains unclear which signaling pathways are influenced by ARID1A mutations and which pathway molecules are targeted by ARID1A mutations in EC pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in EC, the majority of previous studies have focused on the loss of ARID1A expression as determined by immunohistochemistry or gene sequencing of mutations (7)(8)(9)(10)(11). Therefore, it remains unclear which signaling pathways are influenced by ARID1A mutations and which pathway molecules are targeted by ARID1A mutations in EC pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Those complexes are involved in various processes that require alteration of chromatin structure, including DNA repair, DNA synthesis, mitosis and genomic instability. [9][10][11] Most mutations in ARID1A are insertions or deletions, resulting in a truncated protein that is prone to rapid degradation. Therefore, ARID1A gene mutations are highly correlated with loss of protein expression as assessed by immunohistochemistry, even in the absence of mutation in the other allele (eg, haploinsufficiency).…”
mentioning
confidence: 99%
“…The SWI/SNF complex has multiple activities, including the following: The promotion of binding of transcription factors, coactivators and compressors; mobilization of histone-modifying enzymes; promotion of binding of nucleosomes with promoter and enhancer regions; and promotion of chromatin loop formation to induce interactions of enhancers and promoters ( Fig. 1) (7,21). The SWI/SNF complex and ARID1A also regulate transcription to induce steroid hormones: It has been suggested that ARID1A may be involved in recruiting SWI/SNF to regulate genes through its ability to stimulate steroid hormone receptor-mediated transcriptional activation (22,23).…”
Section: Chromatin Remodeling-associated Gene Mutations and Carcinogementioning
confidence: 99%